2022
DOI: 10.3390/children9091346
|View full text |Cite
|
Sign up to set email alerts
|

Remote Learning Experience and Adolescents’ Well-Being during the COVID-19 Pandemic: What Does the Future Hold?

Abstract: Background. Major shifts within the education system have taken place during the COVID-19 pandemic; frontal teaching was often replaced with remote learning, which has affected students in many ways. We investigated the associations and predictors of perceptions of the remote learning experience on well-being (life satisfaction, self-rated health, psychosomatic, and psychological symptoms). Methods. We conducted a cross-sectional research study consisting of 1019 school students in Israel aged 11–18 (53.5% gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The control group did not show any difference in the reported level of crisis concerns before and after the intervention; however, their initial crisis levels at pre-test were significantly lower than those of the intervention group. Recent studies have shown that youth have experienced high rates of anxiety and depression symptoms during the COVID-19 pandemic [ 39 , 40 ]. The resulting social isolation and economic uncertainty have led to a significant increase in mental health concerns [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The control group did not show any difference in the reported level of crisis concerns before and after the intervention; however, their initial crisis levels at pre-test were significantly lower than those of the intervention group. Recent studies have shown that youth have experienced high rates of anxiety and depression symptoms during the COVID-19 pandemic [ 39 , 40 ]. The resulting social isolation and economic uncertainty have led to a significant increase in mental health concerns [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%